COD, BOD and Heavy Metal Removal from Ground Water Treatment by using WASRA System: A Case Study on Universiti Malaysia Pahang Mosque - Abdul Syukor, Abd Razak; Norbaizurah, Rahman; Nur Azzimah, Zamri; Suryati, Sulaiman; Noor Asyikin Aisyah, Burhanudin; Hasmanie, Abdul Halim; Edriyana, Abd Aziz (AENSI, 2015)
Development of a user friendly technology water supply system in the rural Area (WASRA) functioning to treat the groundwater with low cost and economical based on pre-treatment process and membrane technology. This study analyzed the quality of water sources and determine the effectiveness of WASRA System as water supply at UMP Mosque. The effect of WASRA System was evaluated through Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), Manganese and Ferumtesting. Based on the testing of untreated water illustrates that BOD value exceeds the value in CLASS II, which is not suitable for ablution purpose. Meanwhile, the treated water shown that all the parameters achieved the CLASS I standard except for COD which still remain in CLASS II. Therefore, it is concluded that the treated water from WASRA System can be channelled for ablution purposed in the UMP mosque.